Coronary artery bypass graft (CABG) and the diabetic patient: current perspectives - Hoffman DM; Tranbaugh RF (Research Reports in Clinical Cardiology, 2014)
Darryl M Hoffman, Robert F Tranbaugh Division of Cardiothoracic Surgery, Beth Israel Medical Center, New York, NY, USA Abstract: Diabetes increases both the severity and the risks of coronary artery disease. For such patients, revascularization by coronary artery bypass grafting (CABG) has consistently improved survival and event free survival in multiple studies compared to percutaneous revascularization (PCI). Evolving treatments, the growing volume of patients with diabetes who have coronary disease, and the cost of their care mandates regular reevaluation of the evidence on which treatment by CABG or PCI is based. This review provides current perspectives on the role of CABG based on analysis of information from newly reported major trials such as Taxus drug eluting stent versus coronary artery bypass surgery (SYNTAX) and Future revascularization evaluation in patients with diabetes mellitus:optimal management of multiple vessel disease (FREEDOM). Also evaluated are technical advances in CABG and improvements in the care of CABG patients with diabetes which should be incorporated in "best practice" surgical revascularization. The accumulated evidence shows clear superiority of CABG for patients with diabetes and multivessel disease, and in particular the benefits of CABG employing multiple arterial conduits. Keywords: Diabetes mellitus, coronary atherosclerosis, revascularization, coronary stent